Democratic Spirit, Emotions, Help, and Hope during the Russian war against Ukraine: Experience from the Czech Republic - Klicperova-Baker, Martina; Urban, Marek (Applied psychology. Health and well-being, 2024)
This study is based on an original eight-wave longitudinal survey conducted in the Czech Republic (N = 1622, national quota sample). Structural equation modeling (SEM) was employed to create a mediation model to test whether democratic spirit assessed in March 2021 (1 year before the Russian invasion) predicted responses to the major crisis (measured immediately, 2 months, and 9 months after the invasion). The Russian invasion of February 2022 deeply impacted Czech democrats. They reacted by a strong increase in positive emotions toward Ukraine/Ukrainians (e.g., compassion, admiration to courage), a milder increase in negative emotions (e.g., anger) and physiological discomfort. The Russian invasion further strengthened the democratic identity of the Czech citizens which increased their willingness to help Ukraine, both personally and by government. Finally, the democratic spirit of 2021 predicted hope for Ukraine and for Czechia in late 2022 when various crises cumulated. Notably, the direct effect of democratic spirit on future hope was non-significant unless respondents were concerned with some aid to Ukrainians. Help completely mediated the democratic spirit and was linked to hope. The relationship between democratic values and hope was strong and spanned almost 2 years and cumulated crises. The study suggests that democratic values are significantly related to positive reactions to stressful conditions. The protective effect of the democratic spirit seemed beneficial both to one's health and delivering help to victims.
Keywords: war; emotions; Male; Hope; emoce; lidé středního věku; Ukraine; resilience; Russia; Humans; Armed Conflicts; Middle Aged; Czech Republic; Česká republika; mužské pohlaví; Female; ženské pohlaví; naděje; stress; mladý dospělý; Adult; Longitudinal Studies; Young Adult; democratic values; Ukrajina; ozbrojené konflikty; longitudinální studie; lidé; dospělí; Rusko; Emotions